1981
DOI: 10.1111/j.1095-8339.1981.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigment distribution, light reflection and cell structure in petals

Abstract: Petal structure and the distribution of pigments in petals were studied in relation to the functional anatomy of petals and the ways in which petals absorb and reflect light. We examined 201 species from 60 angiosperm families. Anthocyanins, betalains and ultraviolet-absorbing flavonoids were normally confined to the epidermal cells, occurring in solution in the vacuole; carotenoids were found in the epidermis and in smaller quantities in the mesophyll, normally in chromoplasts. In a few species, mainly blue-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
280
2
34

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(324 citation statements)
references
References 17 publications
8
280
2
34
Order By: Relevance
“…Differences in pigmentation between the two lines should not affect this comparison because red light is not absorbed significantly by the floral pigments in either line. Although papillate epidermal cells have frequently been observed in flowers and the possible effects of these cells on the optical properties of petals have been discussed (Exner and Exner, 1910;Brehm and Krell, 1975;Kay et al, 1981), to our knowledge this is the first report quantifying spectra of discs from Mixta+ ( -) and mixta- (----) petals. AI1 plants were grown under low-UV conditions.…”
Section: Epidermal Focusingmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in pigmentation between the two lines should not affect this comparison because red light is not absorbed significantly by the floral pigments in either line. Although papillate epidermal cells have frequently been observed in flowers and the possible effects of these cells on the optical properties of petals have been discussed (Exner and Exner, 1910;Brehm and Krell, 1975;Kay et al, 1981), to our knowledge this is the first report quantifying spectra of discs from Mixta+ ( -) and mixta- (----) petals. AI1 plants were grown under low-UV conditions.…”
Section: Epidermal Focusingmentioning
confidence: 99%
“…Work with visible light has demonstrated that leaf epidermal cells, which are generally domed, can act individually as miniature lenses that can focus direct light on small patches of mesophyll at intensities several times that of the ambient irradiance (Haberlandt, 1928;Martin et al, 1989;Poulson and Vogelmann, 1990;Myers et al, 1994;Vogelmann et al, 1996). Similar to leaves, flower petals often have large, lens-like, conical-papillate epidermal cells, which protrude from the peta1 surface (Kay et al, 1981). In flowers, the intense absorption of both UV (Brehm and Krell, 1975) and visible light (Noda et al, 1994) has been linked to the shape of these strongly domed cells, and in both cases the flattened cells are reported to absorb the light less strongly.…”
mentioning
confidence: 99%
“…The cells of the inner epidermis of the limb or lobe also develop a specialized conical form compared to the normal flattened shape of epidermal cells. These conical cells contain the highest concentrations of anthocyanins, and they reflect incident light to enhance the impact of their pigment as a flash signal (Kay et al, 1981).…”
Section: Petal Developmentmentioning
confidence: 99%
“…Two kinds of petals (a dorsal petal, called a 'standard' and two lateral petals or 'wings') were examined. The epidermal types of the petals were classified based on cell size, shape (the primary sculpture), and on the fine relief of the cell wall, using the terminology of Barthlott (1977) and Kay et al (1981). To investigate trichomes on the sepals, sections were made by hand using commercial razor blades.…”
Section: Introductionmentioning
confidence: 99%